Squeezing Harder Doesn't Always Work: Continuing the Search for Consistency in Innovation Research - Fiol, C. Marlene (Academy of Management Review, 1996)
Organizations, like sponges, must have the capacity to absorb inputs in order to generate outputs. Researchers have developed theories of organizational absorptive capacity; researchers have also developed models of the effective generation of new products. The challenge lies in integrating the two research streams.